Chloroquine-Mediated Cell Death in Metastatic Pancreatic Adenocarcinoma Through Inhibition of Autophagy - Frieboes, Hermann B; Huang, Justin S; Yin, Wenyuan C; McNally, Lacey R (JOP. Journal of the Pancreas, 2014)
Context Cells in the interior of pancreatic tumors are believed to undergo continual autophagy to maintain homeostasis during unregulated growth in hypoxia caused by impaired vascularity. We hypothesize that treating metastatic cells with chloroquine, an inhibitor of autophagy, in hypoxia will decrease cell viability and induce cell death. Design MiaPaCa2 (non-metastatic) and S2VP10 (metastatic) cell lines were treated with 25 and 50 µM chloroquine for 24 and 48 hours in normoxia and hypoxia (5-10% O2). Viability was measured using ATPliteTM. After treatment, the cell stress was analyzed, and protein was lysed and quantified using the Bradford assay. Autophagy-associated protein levels were determined by Western blot. Results S2VP10 cells treated for 48 hours with 50 μM chloroquine in hypoxia had 24% viability compared to normoxia control, with loss of 10% viability caused by low O2 alone. MiaPaCa2 cells under these conditions had 60% viability compared to normoxia control, with loss of 25% viability caused by low O2 alone. Analysis of cell stress pathways and dosimetry of Western blot data suggest that chloroquine inhibits the autophagy pathway in the metastatic S2VP10 cells. Conclusion Autophagy blockage with chloroquine or similar-acting drugs may serve as a viable therapy for highly metastatic pancreatic cancers. Image: MiaPaCa2 cells treated with 25 μM chloroquine for 24 hours (Figure 1e)